2020
DOI: 10.1002/trc2.12102
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Alzheimer's disease data landscape

Abstract: Introduction Numerous studies have collected Alzheimer's disease (AD) cohort data sets. To achieve reproducible, robust results in data‐driven approaches, an evaluation of the present data landscape is vital. Methods Previous efforts relied exclusively on metadata and literature. Here, we evaluate the data landscape by directly investigating nine patient‐level data sets generated in major clinical cohort studies. Results The investigated cohorts differ in key characteristics, such as demographics and distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…Developing robust, trustworthy AI approaches is a challenging task that requires a deep understanding of the application domain, the available data and the technical approach [ 142 , 146 , 150 ]. This marks it a highly interdisciplinary endeavour where multiple experts need to collaborate.…”
Section: Conclusion and Expert Recommendations In The Framework Of 3p Medicinementioning
confidence: 99%
“…Developing robust, trustworthy AI approaches is a challenging task that requires a deep understanding of the application domain, the available data and the technical approach [ 142 , 146 , 150 ]. This marks it a highly interdisciplinary endeavour where multiple experts need to collaborate.…”
Section: Conclusion and Expert Recommendations In The Framework Of 3p Medicinementioning
confidence: 99%
“…It allows researchers to adequately understand and characterize performances measured via external validation of statistical and machine learning models developed on another cohort. In conclusion, our approach allows for better understanding of statistical differences that have previously been reported between various AD studies 13 …”
Section: Introductionmentioning
confidence: 84%
“…Overall, the discovered heterogeneity could likely stem from differences in the recruitment processes of cohort studies. Compositional shifts across sampled populations pose a critical confounder comparing cohort datasets and model performance 13 . Here, statistical matching could potentially help to identify comparable subsets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a recent study, we observed that the information gained through such metadata-driven cohort assessments differs from the content that is factually shared with researchers after successful access applications [15].…”
Section: Introductionmentioning
confidence: 91%